Wave drag in human swimming - Pease, D. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
This presentation will examine the influence of wave drag on human swimming performance. Even though wave drag has been measured on ships for nearly a century it is only relatively recently that it has been examined in regard to human swimming. Wave drag has been shown to contribute to up to 50% of the total drag experienced during free swimming so gaining and understanding of it and what factors influence it is valuable to not only scientists, but coaches and athletes alike.